A Selection Model of Strategic Emerging Industries in Fujian Based on Entropy-VIKOR Algorithm - Qionge Zheng; Kunhui Chen; Deyi Kong; Jingxuan Liang; Jingjing Wu (Discrete Dynamics in Nature and Society)
The cultivation of strategic emerging industries is strategic to the economic transformation and upgrading in Fujian, a southeastern province of China. It is of great significance to study its selection model. In this paper, according to the characteristics of strategic emerging industries, drawing on the double helix model, this paper sets up an evaluation system for strategic emerging industries. Then, the entropy-VIKOR algorithm was introduced to evaluate and rank the backbone enterprises in Fujian, based on the data on 21 listed enterprises of strategic emerging industries in the province from 2017 to 2019. The empirical research results are consistent with the actual situation of the development of strategic emerging industries in Fujian Province, which proves the feasibility of this research method. Finally, according to the empirical analysis results, this study puts forward some countermeasures for the development of strategic emerging industries in Fujian province.